2018
DOI: 10.1007/s00167-018-5057-5
|View full text |Cite
|
Sign up to set email alerts
|

No difference in sensory outcome between vertical and oblique incisions for hamstring graft harvest during ACL reconstruction

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…The number of incisional injuries observed in this study is in line with clinical reports [9, 10, 12, 20–22, 24, 26], but it is unknown how macroscopically visible lesions in cadaver limbs compare to sensibility loss in a clinical study. While the number of incisional injuries observed was high, only one‐fourth of these injuries were complete discontinuations of IPBSN and MCCB.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The number of incisional injuries observed in this study is in line with clinical reports [9, 10, 12, 20–22, 24, 26], but it is unknown how macroscopically visible lesions in cadaver limbs compare to sensibility loss in a clinical study. While the number of incisional injuries observed was high, only one‐fourth of these injuries were complete discontinuations of IPBSN and MCCB.…”
Section: Discussionsupporting
confidence: 87%
“…Altered sensation following ACL reconstruction with medial hamstrings is usually attributed to IPBSN injuries. It affects 12–88% of patients [9, 10, 12, 20–22, 24, 26] and has been linked to the incision used for hamstring tendon harvest [4, 12, 14, 17, 20, 26]. A vertical incision appears to increase the risk of iatrogenic IPBSN injuries significantly [6, 18, 19], and therefore, it is recommended to use an oblique incision parallel to the expected course of the IPBSN [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our hypothesis that there would be a difference in the presence or absence of hypoesthesia or in the affected surface area of sensory loss between the vertical and oblique incision groups was not supported. This is in agreement with a recent systematic review investigating saphenous nerve injury during ACL reconstruction 15,17 but contrary to the results of a more recent meta-analysis. 13 The cadaveric study supported the results of this meta-analysis because it confirmed that a safe zone for the incision angle is unlikely due to the large variability in the number and different angles of branches of the IBSN between cadavers.…”
Section: Discussionsupporting
confidence: 84%
“…As concluded by a meta‐analysis on 11 studies, surgeons should avoid employing the vertical incision, which was associated with the highest rate of infrapatellar branches of the saphenous nerve (IPBSN) iatrogenic injury (51.4%) [43]. In contrast, Sharaby et al [47] revealed the high incidence of IPBSN injury during hamstring graft harvest, but did not prove a difference between oblique and vertical incisions, with regard to postoperative sensory loss. In addition to infrapatellar branches, injury of sartorial branch (SBSN) has been raised [39, 42] but rarely reported [7].…”
Section: Discussionmentioning
confidence: 99%